Do Prostate Cancer Patients With Markedly Elevated PSA Benefit From Radiation Therapy?: A Population-based Study. (December 2017) - Lawrence, Yaacov R.; Samueli, Benzion; Levitin, Ronald; Pail, Orrin; Spieler, Benjamin; Pfeffer, Raphael; Goldstein, Jeffrey; Den, Robert B.; Symon, Zvi
Abstract : Objectives: Patients with clinically localized prostate cancer but markedly elevated prostate-specific antigen (PSA) are often treated with systemic agents alone. We hypothesized that they would benefit from radiation therapy. Methods: We utilized the Survival, Epidemiology and End Results (SEER) Database for patients diagnosed with nonmetastatic prostate cancer from 2004 to 2008. Patients treated surgically or with brachytherapy were excluded. Survival was analyzed using the Kaplan-Meier method and Cox proportional hazard models. Propensity score was used to adjust for the nonrandomized assignment of local therapies. Results: A total of 75, 539 nonmetastatic prostate cancer patients were identified who received either radiotherapy or no local treatment. Median age was 70 years. Median follow-up of alive subjects was 60 months, with an interquartile range of 47 to 77 months. Estimated 4-year overall survival of entire population was 88%. Significant prognostic variables for overall survival on multivariate analysis included age, grade, PSA level, T stage, and use of radiation therapy. Use of radiation therapy was the most powerful predictor of both cause-specific and overall survival (HR=0.41 and 0.46, respectively, P <0.001). The benefit conferred by local treatment was seen even in subjects with PSA≥75 ng/mL. Four-year cancer-specific survival was 93.8% in those receiving radiation treatments versus 76.5% in those who did not receive any local treatment. Conclusions: Survival was significantly improved by radiotherapy for localized prostate cancer. Extremely high PSA levels (≥25 ng/mL) should not be considered a contraindication to local treatment. Abstract : Supplemental Digital Content is available in the text.